Management of enterprise in the conditions of a free economic zone - Gromadchuk, Tatiana; Heřman, Jan; Alexeev, Vladimir; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
Objective: To evaluate the effect of external factors on the management of the enterprise in the free economic zone. The object of the research is Sherrizone, and the subject will be performing organizational and economic relations in the interaction with the effects of external influences on the management of the enterprise in the free economic zone. Sherrizone performs the basic idea of creating a free economic zone and creates a limited area, in the vicinity of the Sheremetyevo International Airport, the world standards production, business and social infrastructure necessary for effective activities of foreign and domestic investors
Vedoucí práce: Jan Heřman
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: ekonomika predprijatija i menedžment [obor bakal. práce]; bakalářské práce; bachelor's theses